Bridging Campus and Classroom: Interactive Science Media Developed by Elementary Teacher Education Students to Foster Inspiring Science - Khairunnisak; Kiki Fajariani (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to describe the process and impact of developing interactive science media by students of the Elementary School Teacher Education (PGSD) program in primary school science learning. A descriptive qualitative approach with a collaborative-participatory research design was employed. The research subjects consisted of sixth-semester PGSD students and fourth- and fifth-grade students of SD Negeri 8 Juli. Data were collected through observation, interviews, documentation, and students’ reflective journals, and analyzed using descriptive qualitative methods. The findings reveal that the media developed by the students - such as a solar system miniature, an electrical conductivity tester, and a science-themed board game - effectively enhanced students' engagement and understanding of science concepts. Moreover, the direct involvement of PGSD students in classroom media implementation strengthened their pedagogical and professional competencies as future teachers. Collaboration with school teachers also played a pivotal role in creating contextual, creative, and enjoyable learning experiences. These findings highlight the tangible contribution of student-developed media projects to improving the quality of science education in primary schools.